2019
DOI: 10.1038/s41467-019-10158-4
|View full text |Cite
|
Sign up to set email alerts
|

Atomic dispensers for thermoplasmonic control of alkali vapor pressure in quantum optical applications

Abstract: Alkali metal vapors enable access to single electron systems, suitable for demonstrating fundamental light-matter interactions and promising for quantum logic operations, storage and sensing. However, progress is hampered by the need for robust and repeatable control over the atomic vapor density and over the associated optical depth. Until now, a moderate improvement of the optical depth was attainable through bulk heating or laser desorption – both time-consuming techniques. Here, we use plasmonic nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…There are potential applications for this technology, which do not fall within the subsections we chose for this review. As an example, gold nanoparticles based coatings were recently prepared to control the alkali atom vapor pressure for quantum sensors . This work constitutes an early exploration at the interface between plasmonics and atomic quantum optics.…”
Section: Resultsmentioning
confidence: 99%
“…There are potential applications for this technology, which do not fall within the subsections we chose for this review. As an example, gold nanoparticles based coatings were recently prepared to control the alkali atom vapor pressure for quantum sensors . This work constitutes an early exploration at the interface between plasmonics and atomic quantum optics.…”
Section: Resultsmentioning
confidence: 99%
“…29 In many scenarios, reaction rates depend on local temperature, which can be controlled with the aid of plasmonic absorption. 30,31 In this case, the interaction has to be tailored in order to efficiently distribute the temperature along at least several centimeters of a fiber. In other words, the plasmonic layer must be sufficiently absorptive to induce heating, but not too absorptive to dissipate the entire light intensity close to the fiber facet.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work has revealed that RIBs using monolayer MoS 2 anode materials not only have comparable theoretical capacities but also have approximately one order of magnitude lower diffusion energy barriers compared to commercial LIBs (graphite anodes) . Recently, McGilligan and Kang disclosed RIBs that can be utilized as a Rb-atom source. Their advantages of being fast and having a low power, high purity, small size, and reversibility make them one of the key technologies for the development of quantum fields, such as miniaturized cold/ultra-cold atom physics systems, efficient photon–photon logic gates, and efficient quantum memories. …”
Section: Introductionmentioning
confidence: 99%
“… 12 15 Their advantages of being fast and having a low power, high purity, small size, and reversibility make them one of the key technologies for the development of quantum fields, such as miniaturized cold/ultra-cold atom physics systems, efficient photon–photon logic gates, and efficient quantum memories. 16 18 …”
Section: Introductionmentioning
confidence: 99%